Experimental Investigation of Thrust Force in the Drilling of Titanium Alloy Using Different Machining Techniques - Lijie Ma; Zunyan Ma; Hui Yu; Shenwang Li; Minghua Pang; Zhankui Wang (Metals, 2022)
Titanium alloy is a kind of hard-to-cut material widely used in aerospace, military and medical fields, and mechanical drilling is the primary technique used for hole-making in titanium alloy materials. The drilling force is an inevitable concomitant phenomenon in the drilling process and thrust force is its most important component. During the drilling of titanium alloy, it is crucial to understand the fundamental characteristics and changing rules of thrust force for optimizing process parameters, improving machining quality and predicting tool failure. In this paper, four different techniques, such as direct drilling (DD), ultrasonic vibration drilling (UVD), peck drilling (PD) and ultrasonic vibration peck drilling (UVPD), were used to drill small holes into Ti-6Al-4V titanium alloy, the thrust force was measured and its mean, maximum and peak-to-valley value were acquired from the time-domain waveform. Then the time-domain and frequency-domain characteristics of thrust force under the four techniques were compared, and the changing rules of thrust force with vibration amplitudes during UVD and UVPD were investigated. The results showed that, when compared to DD, UVD decreased the mean thrust force Famean by about 18.6%, and the force reduction effect was more significant as the amplitude increased. The variable velocity cutting characteristics and the antifriction effect of UVD were the primary reasons for the reduction of Famean. The pecking motion and ultrasonic vibration had a synergistic effect on reducing thrust force; UVPD could simultaneously reduce the mean thrust force Famean and maximum thrust force Famax. When the amplitude A was chosen within the range of 2–3 μm, Famax and Famean were reduced by approximately 37% and 40% in comparison to DD.